The rediscovery of Schaefer’s Spine-jawed Snake (Xenophidion schaeferi Günther & Manthey, 1995) (Serpentes, Xenophidiidae) from Peninsular Malaysia with notes on its variation and the first record of the genus from Sumatra, Indonesia - Quah, Evan S.h.; Grismer, L. Lee; Jetten, Thom; Wood, Perry L. Jr.; Miralles, Aurélien; Sah, Shahrul Anuar Mohd; Guek, Kurt H.p.; Brady, Matthew L. (Zootaxa, 2018)
The family Xenophidiidae is an extremely rare and little-known family of snakes that contains only two species, Xenophidion acanthognathus Günther & Manthey and X. schaeferi Günther & Manthey that are each known only from their holotypes. We report on the rediscovery of X. schaeferi from two new locations in southern Peninsular Malaysia. The new specimens differ markedly from the holotype of X. schaeferi in colour pattern and are more akin to the patterning of X. acanthognathus from Borneo. However, molecular analyses of one of the new specimens reveal that it only differs from the holotype of X. schaeferi by a minimum sequence divergence of 0.27%. An expanded description of the species based on these specimens is provided and phenotypic variation within the species is discussed. We also report the first record of the genus Xenophidion from West Sumatra, Indonesia. These sensational discoveries continue to underscore the fact that southern Peninsular Malaysia and upland areas of Southeast Asia in general still harbour unrealized herpetological diversity and are still in need of field research-based taxonomic studies.